Spelled eaudiobook - Peters, Camille (Kingdom Chronicles, 2020)
Rosie is fairly certain that there's nothing wrong with putting a love spell on a foreign prince. At least she hopes there's not, because such a drastic measure is necessary in order for her to ensure that the perfect fairy tale romance she's dreamt about her entire life includes her own prince charming. As the heroine in her story, she won't be deterred by well-meaning friends, royal betrothals, hungry dragons, or the intriguing guard who stands in her way. Luckily, Rosie has access to an enchanted bakery and a recipe book of spells, one of which will ensure she'll win the royal heart she desires. Unfortunately, no story is complete without a few obstacles, and Rosie's comes in the form of a most formidable foe—a stoic guard whom Rosie may or may not be developing feelings for, one who is committed to thwarting her at every turn. But nothing will stand in the way of Rosie's happily ever after. After all, what harm can a simple love spell do?